GENERAL PROFESSIONAL COMPETENCE OF A MODERN RUSSIAN ENGINEER - A. I. RUDSKOY; A. I. BOROVKOV; P. I. ROMANOV; O. V. KOLOSOVA (Высшее образование в России, 2018)
The National Presidential Council for professional competence coordinates development of new professional standards and modernization of existing ones. A task was set to prepare and update Educational Standards on the basis of revised Professional Standards. 158 Federal State Educational Standards on Engineering and Industrial Technology Sciences have been developed so far. It is suggested to use this massive data to formulate a generalized competence-based model of an engineer with a particular educational degree in a particular field of education. To develop the model a standardization of wording for all general professional competences similar for all engineering majors had to be completed. The results of the survey described in this article will be the basis for recommendations of Coordination Board in Engineering and Industrial Technology Sciences. A project of general professional competences unified for the field of education is presented in the summary of the article.